Immunological Consequences of Nanoparticle‐Mediated Antitumor Photoimmunotherapy. Issue 5 (20th August 2019) - Hameed, Sadaf; Mo, Shanyan; Mustafa, Ghulam; Bajwa, Sadia Z.; Khan, Waheed S.; Dai, Zhifei
Abstract: Conventional phototherapies have been thought to destroy the malignant cells through apoptosis or necrosis, shut down tumor microvasculature, and activate the host immune system. Accumulating evidence indicates that photothermal agents stimulate both innate and adaptive arms of host immune systems by i) priming tumor antigen–specific T‐cell responses, ii) attracting lymphocytes into the tumor site, and iii) modulation of the tumor microenvironment (TME). However, the salutary effect of traditional phototherapies is hindered by its limited penetration depth in tissues. Recent advances in cancer immunotherapies have significantly transformed the landscape of cancer treatment from conventional phototherapies to most standard cancer therapy regimen. Therefore, phototherapies synergized with immunotherapy, maximize the anticancer efficacy by overcoming immunosuppressive TME and elucidating immune responses outside the irradiation area. This synergism is further strengthened by nanomaterial‐based strategies to form innovative nanocarriers for efficient and simultaneous delivery of photosensitizers and immunomodulators at the desired target. These nanocarriers can improve the accumulation and retention of both photosensitizer and immunomodulators within the target location, thereby enhancing safety and efficacy. Herein, the systematic effects of phototherapies on the immune system are summarized and the ways in which nanomaterial‐based photoimmunotherapy can facilitate the eradication of both primary and metastatic tumors are discussed. Abstract : Phototherapies synergized with immunotherapy, through different mechanisms, maximize anticancer efficacy by overcoming the immunosuppressive tumor microenvironment and elucidating immune responses outside the irradiation area. This synergism is further strengthened by manipulating nanomaterial‐based strategies to form innovative nanocarriers for efficient and simultaneous delivery of photosensitizers and immunomodulators at the desired target, thereby enhancing the safety and efficacy of the treatment.